Symptoms and signs of conjunctivitis as predictors of disease course in COVID-19 syndrome - Martina Ranzenigo; Elena Bruzzesi; Laura Galli; Antonella Castagna; Giulio Ferrari (Journal of Ophthalmic Inflammation and Infection, 2021)
Abstract Background Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) can induce conjunctivitis signs and symptoms. However, limited information is available on their impact on COVID-19 disease phenotype. Quantification of ocular signs/symptoms can provide a rapid, non-invasive proxy for predicting clinical phenotype. Moreover, the existence and entity of conjunctival viral shedding is still debated. This has relevant implications to manage disease spread. The purpose of this study was to investigate conjunctivitis signs and symptoms and their correlation with clinical parameters, conjunctival viral shedding in patients with COVID-19. Methods Fifty-three patients hospitalized between February 25th and September 16th, 2020 at the San Raffaele Hospital, in Milan, Lombardy, Italy with a confirmed diagnosis of SARS-CoV-2 were evaluated. Presence of interstitial pneumonia was confirmed with computed tomography scan imaging. Ocular signs and symptoms, anosmia/ageusia, clinical/laboratory parameters, and reverse transcriptase–polymerase chain reaction (RT-PCR) from nasopharyngeal and conjunctival swabs for COVID-19 virus were analyzed. Results Forty-six out of 53 patients showed a positive nasopharyngeal swab for SARS-CoV-2 infection at the time of conjunctival evaluation. All the conjunctival swabs were negative. Conjunctivitis symptoms were present in 37% of patients. Physician-assessed ocular signs were detected in 28% of patients. Patients with ocular symptoms or signs tended to be older: 76.8 years (62.4–83.3) vs 57.2 years (48.1–74.0), p = 0.062 and had a longer hospitalization: 38 days (18–49) vs. 14 days (11–21), p = 0.005. Plasma levels of Interleukin-6 were higher in patients with signs or symptoms in comparison with those without them: 43.5 pg/ml (19.7–49.4) vs. 8 pg/ml (3.6–20.7), p = 0.02. Red cell distribution width was also significantly higher: 15 (14.3–16.7) vs 13.2 (12.4–14.4), p = 0.001. Conclusions We found that over a third of the patients had ocular signs or symptoms. These had higher prevalence in patients with a more severe infection. No viral shedding was detected in the conjunctiva. Our results suggest that prompt detection of conjunctivitis signs/symptoms can serve as a helpful proxy to predict COVID-19 clinical phenotype.